Therapy for Stage IV Non–Small-Cell Lung Cancer Without Driver Alterations: ASCO Living Guideline, Version 2022.2. Issue 5 (10th February 2023) - Owen, Dwight H.; Singh, Navneet; Ismaila, Nofisat; Blanchard, Elizabeth; Celano, Paul; Florez, Narjust; Jain, Dharamvir; Leighl, Natasha B.; Mamdani, Hirva; Masters, Gregory; Moffitt, Pamela R.; Naidoo, Jarushka; et al.
Abstract : Living guidelines are developed for selected topic areas with rapidly evolving evidence that drives frequent change in recommended clinical practice. Living guidelines are updated on a regular schedule by a standing expert panel that systematically reviews the health literature on a continuous basis, as described in the ASCO Guidelines Methodology Manual . ASCO Living Guidelines follow the ASCO Conflict of Interest Policy Implementation for Clinical Practice Guidelines . Living Guidelines and updates are not intended to substitute for independent professional judgment of the treating provider and do not account for individual variation among patients. See Appendix 1 (online only) for disclaimers and other important information. Updates are published regularly and can be found at https://ascopubs.org/nsclc-non-da-living-guideline .